(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the epidemiological aspects and spatial distribution of cases of canine lymphoma in the Metropolitan Region of Recife-PE, Brazil. Epidemiological data obtained from medical records of 178 dogs were analyzed, including 89 cases and 89 controls. For the analysis of risk factors, information related to contact with carcinogens, food, and housing of the animal was considered. The map was prepared using georeferencing points obtained from municipalities, neighborhoods, and postal address codes in the clinical records of the animals. The risk factors identified consisted of contact with humans undergoing chemotherapy/radiotherapy (OR=13.54; p=0.014), mixed feeding (OR=5.59; p=0.000), animal contact with paints and solvents (OR= 5.08; p=0.014), living close to a busy avenue or street (OR=4.86; p=0.000), and home-cooked meals (OR=2.44; p=0.014). The highest number of lymphoma cases was found in the southern region of the city of Recife, as well as in the northern region of Olinda. The occurrence of canine lymphomas diagnosed in the Metropolitan Region of Recife is closely related to exposure to environmental carcinogens.